Star-spot activity, orbital obliquity, transmission spectrum, physical properties, and transit time variations of the HATS-2 planetary system - Biagiotti, Francesco; Mancini, Luigi; Southworth, J.; Tregloan-Reed, J.; Naponiello, L.; Jørgensen, U. G.; Bach-Møller, N.; Basilicata, M.; Bonavita, M.; Bozza, V.; Burgdorf, M. J.; Dominik, M.; et al. (Astronomy and astrophysics, 2024)
Aims. Our aim in this paper is to refine the orbital and physical parameters of the HATS-2 planetary system and study transit timing variations and atmospheric composition thanks to transit observations that span more than 10 yr and that were collected using different instruments and pass-band filters. We also investigate the orbital alignment of the system by studying the anomalies in the transit light curves induced by starspots on the photosphere of the parent star.